2015
DOI: 10.3390/s150715363
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Quality Assessment via Dielectric Sensing

Abstract: The demand for improved food quality has been accompanied by a technological boost. This fact enhances the possibility of improving the quality of horticultural products, leading towards healthier consumption of fruits and vegetables. A better electrical characterization of the dielectric properties of fruits and vegetables is required for this purpose. Moreover, a focused study of dielectric spectroscopy and advanced dielectric sensing is a highly interesting topic. This review explains the dielectric propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 90 publications
(112 reference statements)
2
53
0
2
Order By: Relevance
“…The variations in reflected voltage, V r of tea leaves bulk with the percentage of m.c at various operating frequencies, respectively, are plotted in Figure 5a-e. As expected, the reflected voltage, V r of tea leaves increases exponentially with m.c, since relative permittivity, ε r of agricultural product normally increases exponentially with its m.c [20] at higher operating frequencies. From Figure 5, we found that the measurement frequency at 1.529 GHz is able to provide stable and sensitive measurement with respect to m.c of the all tea leaves.…”
Section: Resultssupporting
confidence: 74%
“…The variations in reflected voltage, V r of tea leaves bulk with the percentage of m.c at various operating frequencies, respectively, are plotted in Figure 5a-e. As expected, the reflected voltage, V r of tea leaves increases exponentially with m.c, since relative permittivity, ε r of agricultural product normally increases exponentially with its m.c [20] at higher operating frequencies. From Figure 5, we found that the measurement frequency at 1.529 GHz is able to provide stable and sensitive measurement with respect to m.c of the all tea leaves.…”
Section: Resultssupporting
confidence: 74%
“…The complex permittivity measures the ability of a material to absorb and store potential electrical energy and is composed of a real permittivity (ϵ′) part, that describes the ability of a material to store energy when it is subjected to an electric field and influences the electric field distribution and the phase of waves travelling through the material, and an imaginary permittivity (ϵ′′) part, that influences both energy absorption and attenuation and describes the ability to dissipate energy in response to an applied electric field through various polarization mechanisms that commonly result in heat generation . Loss tangent (tanδ=ϵ''/ϵ') indicates the ability of the material to transform energy into heat.…”
Section: Electromagnetic Shielding Materialsmentioning
confidence: 99%
“…The interaction of electromagnetic waves with matter is sensitive to various physical and chemical parameters ([1,2]). Hence, high frequency (radio and microwave) electromagnetic methods (HF-EM) present a strong potential for quantitative estimation for water content for porous media in geoenvironmental engineering [3].…”
Section: Introductionmentioning
confidence: 99%